2020
DOI: 10.18805/lr-4181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic and Inorganic Nutrient Sources on Growth, Yield, Nutrient Uptake and Economics of Fodder Cowpea [Vigna unguiculata (L.) Walp.]

Abstract: An experiment was conducted to evaluate the varying organic and inorganic nutrient sources on fodder cowpea [Vigna unguiculata (L.) Walp.] in the kharif of 2017 at ICAR- NDRI, Karnal. The result revealed that application of 100% RDF (N,P,K) along with biofertilizers (rhizobium, PSB, potassium and zinc solubilizer bacteria) (T6) gave significantly (P less than 0.05) higher in plant height (204.6 cm), primary branches (6.1), root length (24.47 cm), green matter yield (334.5 q ha-1), CGR (8.13 g m-2 day-1), RGR (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…in plants and thus contributed to higher dry matter accumulation and yield. Present findings are in tune with that of Hamidi et al (2006), Yadav et al (2007) and Dutta et al (2019).…”
Section: Resultssupporting
confidence: 93%
“…in plants and thus contributed to higher dry matter accumulation and yield. Present findings are in tune with that of Hamidi et al (2006), Yadav et al (2007) and Dutta et al (2019).…”
Section: Resultssupporting
confidence: 93%
“…On pooled data basis, it was reported that combination of organic, inorganic and seaweed application (N3, N2 and N4) (25.95, 25.21 and 24.71) significantly enhanced the nodule counts from the inorganic treatment (N1) (21.88) and also at par with organic treatment (N5) (24.32) at 50 DAS of crop. However, at the time of harvest, integrated nutrient management treatment (N3) (46.92) had significantly higher nodule count than rest of the treatments and lowest value showed in inorganic treatment (N1) (36.87) (Dutta et al, 2021). There was significant reduction in nodule number at fully inorganic treated plot due to integrated application of organic manures in the form of vermicompost and mustard oil cake improved nodulation as nitrogen was released slowly after decomposition from these manures (Ghosh et al, 2004).…”
Section: Total Nodules Numbermentioning
confidence: 98%
“…Hence, improvement in these components under phosphorus application reflected in higher uptake of nutrients by the crops. Hadwani and Gundalia (2005) and Dutta et al (2020).…”
Section: Nutrient Uptakementioning
confidence: 99%
“…The marked increment of N, P and K concentration in plant parts with the application of increased phosphorus seems to be on account of its pivotal role in the formation of roots, their proliferation, microbial population and activity in the soil. (Meena et al 2016;Dutta et al 2020).…”
Section: Nutrient Concentrationmentioning
confidence: 99%